Pengaruh penggunaan tepung batang talas (Colocasia esculenta) terfermentasi sebagai pengganti jagung terhadap ukuran linear tubuh dan tebal lemak punggung ternak babi peranakan landrace - Hermanus Gelu Bhoja; Sabarta Sembiring; Tagu Dodu (Jurnal Peternakan Lahan Kering, 2019)
This study aimed at evaluating the effect of using fermented taro (Colacasia esculenta) corm substituting corn meal in the diet on body linear size and back fat thickness crossbred landrace pigs. There were 12 grower pigs of 2.5 months of initial age used in the study. Randomized Block Design (RBD) 4 treatments with 3 replicates procedures were applied in the study. The 4 treatments were: R0 = basal diets, R1: 12,5% fermented taro substitute corn meal; R2: 25% fermented taro substitute corn meal; and R3: 37,5%fermented taro substitute corn meal. Variable studied consisted of: body length, chest cycles, shoulder height increase, and back fat thickness. Statistical analysis showed that effect of treatment is not significant (P>0.05) on body length, chest cycles, shoulder height, and back fat thickness. The conclusion is that using fermented taro corm meal up to 37,5% substituting corn meal in the diet perform the similar result in the body length, chest cycles, shoulder height, and back fat thickness crossbred Landrate pigs.